2008
DOI: 10.1111/j.1750-3841.2008.00815.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality of Finfish and Shellfish with Special Reference to Shiga Toxin‐Producing Escherichia coli O157

Abstract: The objective of this study was to determine the microbiological quality of fish and shellfish from Kolkata, India, with special emphasis on E. coli O157. Fresh and ice-preserved Labeo rohita, Catla catla, Cirrhinus mrigala, Oreochromis mossambica, Heteropneustesfossilis, Clarias batrachus, and Penaeus monodon were examined for total heterotrophic bacteria and coliform loads and presence of E. coli and E. coli serotype O157 by culture method. While the total plate count of bacteria was within acceptable or mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
12
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
(21 reference statements)
4
12
0
2
Order By: Relevance
“…Dead-end hosts, as the name suggests, are incapable of transmitting STEC naturally to other animals. In the absence of evidence that aquatic species such as finfish and shellfish transmit the organism to other animals, they may act as dead-end hosts for STEC, only transmitting STEC when they are consumed (4)(5)(6).…”
mentioning
confidence: 99%
“…Dead-end hosts, as the name suggests, are incapable of transmitting STEC naturally to other animals. In the absence of evidence that aquatic species such as finfish and shellfish transmit the organism to other animals, they may act as dead-end hosts for STEC, only transmitting STEC when they are consumed (4)(5)(6).…”
mentioning
confidence: 99%
“…Although not an issue in the U.S. [22], foodborne illnesess from seafood contaminated with STECs are a significant problem in many areas of the world [13][14][15][16][17][18][19][20][21]. To date there are few tools available to predict the risk of STEC growth in seafood as a result of either mild or severe temperature abuse.…”
Section: Resultsmentioning
confidence: 99%
“…50% of seafood production worldwide [12]. Contamination of seafood (either wild caught or aquaculture-raised) with pathogenic E. coli has been known to occur, much of which is due to contaminated water sources, in many parts of the world [13][14][15][16][17][18][19][20][21]. In contrast, illnesses due to STECs from consumption of farm raised catfish in the U.S. are extremely rare [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Animal reservoirs for STEC O157:H7 including amphibians and fish, as well as invertebrates, such as insects and mollusks, were reviewed elsewhere 95,96) . Aquatic species such as finfish and shellfish as dead-end hosts 96) could transmit the organism to other animals, when they are consumed [97][98][99] .…”
Section: -3 Animal Reservoir Of Stecmentioning
confidence: 99%
“…Animal reservoirs for STEC O157:H7 including amphibians and fish, as well as invertebrates, such as insects and mollusks, were reviewed elsewhere 95,96) . Aquatic species such as finfish and shellfish as dead-end hosts 96) could transmit the organism to other animals, when they are consumed [97][98][99] .In a survey performed on rectal content samples from 250 beef cattle on 25 beef farms and 250 dairy cows on 25 dairy farms during summer in 2011 in Japan, STEC O157 was isolated from 16 (6.4%) beef cattle on 7 (28%) beef farms, but not obtained from any dairy cows tested 100) , and the previous investigation performed by the same authors four years apart showed very similar prevalence of STEC O157 (8.9%) 101) . In another study, prevalence of STEC strains in 932 healthy dairy cows from 123 farms was 12%, and 31 different Oserogroups, including O26 but not O157, were identified 102).…”
mentioning
confidence: 99%